Sauchinone alleviates dextran sulfate sodium-induced ulcerative colitis via NAD(P)H dehydrogenase [quinone] 1/NF-kB pathway and gut microbiota - Wu, Kun; Liu, Xianjun; Meng, Xianglong; Cao, Lingling; Li, Hao; Bi, Yingxin; Wang, Mengyuan; Wang, Mingchuan; Jiang, Yang (Frontiers in Microbiology, 2023)
Objective: This study evaluated the effects of sauchinone on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) mice model and investigated the underlying mechanisms of the downstream pathway and gut microbiota. Methods: The UC mice model was induced by DSS. The disease phenotypes were determined through pathological symptoms (body weight and disease activity index score), inflammation markers (histological and inflammatory factor detections), and colonic mucosal barrier damage (detection of tight junction proteins). The level of the NF-κB pathway was detected through marker proteins. Database and bioinformatics analyses were used to predict sauchinone-mediated downstream molecules that were previously identified by expression analysis. Mouse feces were collected to detect the V3–V4 region of the 16S rRNA gene. Results: In DSS-induced UC mice, sauchinone alleviated pathological symptoms, inhibited inflammation, and prevented mucosal barrier damage. Sauchinone further inhibited the NF-κB pathway by upregulating NAD(P)H quinone oxidoreductase 1 (NQO1) in DSS-induced UC mice. Moreover, sauchinone regulated the diversity and composition of the gut microbiota in mice, stimulating the growth of Firmicutes and inhibiting the growth of Proteobacteria and Bacteroidetes. Conclusion: Therefore, sauchinone exerted therapeutic effects on UC in mice by regulating the NQO1/NF-κB pathway and altering the gut microbiota. This provides a theoretical basis for developing sauchinone as a therapeutic agent and extends our understanding of its bioactivity.